Energy taxes and subsidies - Brannon, Gerard Marion; Ford Foundation (Cambridge, Massachusetts : Ballinger Publishing Company, 1974)
This study on energy tax and subsidy policies combines strong arguments for market-oriented energy policies with specific tax and subsidy policy recommendations which, in the author's considered and thoughtful opinion, will make markets more economically efficient allocators of society's scarce resources.
Includes bibliographical references.
ne 27/04/2018
Loans
Keywords: Energy policy; Energy tax; Subsidies; Public utilities